Resisting the Surge of Salafism among Malay and Javanese Muslims: The Dynamics of the Tarekat Naqshbandiya and Qadiriya wa Naqshbandiya in Promoting Peaceful Islam in Riau Sumatera - Rubaidi, Rubaidi; Hilmy, Masdar; Mas’ud, Ali; Basyir, Kunawi (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2023)
This article examines the role of two Sufi orders, the Naqshbandiya order and the Qadiriyya wa al-Naqshbandiya order, in the social and cultural transformation of Malay and Javanese Muslims in contemporary Sumatra, specifically in the Malay Riau region. Socio-political approach is employed in order to analyze the internal and external dynamics of the actors involved in the object of study. The argument presented in this article states that, the Naqshbandi order or ‘Malay Riau Muslim tarekat’ has played a vital role in the social and cultural transformation of Malay Muslims by promoting a peaceful and moderate interpretation of Islam. However, the more legalistic and rigid interpretation of Islam from Saudi Arabia has promoted the Naqshbandi order to adopt a more Shari‘a-oriented approach which has gradually eroded the spiritual essence of the order’s culture and given way to more radical Islamic beliefs in the Malay Riau region. In response, the Qadiriya wa al-Naqshbandiya order continues to represent the authentic Javanese Muslim traditions and beliefs, propagating the original heritage of Malay Islamic tradition and culture. This article found out that the ethnicity embedded in the followers of tarekat may influence the orientation of a particular sufi order.